Biddy Mason speaks up - White, Arisa; Atkins, Laura (Fighting for justice., 2019)
Through informational text and verse, highlights the life and struggles faced by African American philanthropist, civil rights champion, and former slave Bridget "Biddy" Mason. Includes a timeline, sidebars, and color images.